The Effects of Recombinant Human Erythropoietin (rHuEPO) on Antihuman Lymphocyte Antibodies Titer in Sensitized Rats (Journal of Sciences, Islamic Republic of Iran)
Erythropoietin (EPO) was first known as a factor for red blood cell proliferation and differentiation. Recent studies show the effects of EPO on immune system. In this study the antihuman leukocyte antibody (anti-HLA) titer were determined in five groups of rats, which had been sensitized with human lymphocyte. Also, the effects of stimulation's frequency and dose of recombinant human erythropoietin (rHuEPO) on anti-HLA antibody titer were studied. Two groups of rats received 20 and 100 IU/kg rHuEPO respectively, after twice sensitization with human lymphocyte. The other two groups were given 20 and 100 IU/kg rHuEPO, but after three times sensitization with human lymphocyte. Control group did not receive rHuEPO. Microlymphocytotoxicity method was used to detect anti-HLA antibodies. The results show that the anti-HLA antibody titer has been decreased significantly compared to control group. This statistically significant decrease was seen in groups, which received 100 IU/kg rHuEPO, and also in those, which received 20 IU/kg after 2 antigenic stimulations. This could be due to the effects of rHuEPO on the number or the activity of B cells and T cells. Moreover, the dose of rHuEPO, length of treatment and the level of sensitization with human lymphocyte might affect anti-HLA antibody titer.